Rare bird documentation form for Bohemian Waxwing at Glendale Cemetery in Des Moines, 1985 - Zaletel, Hanket al (1985)
Rare bird documentation form for a Bohemian Waxwing at Glendale Cemetery in Des Moines in Polk County, IA on January 27, 1985. Epson - sheet feed